E-Alert Application in Facing Earthquake Disaster - Apriani Apriani; Sandi Justitia Putra; Ismarmiaty Ismarmiaty; Ni Gusti Ayu Dasriani (Universitas Bumigora, 2020)
Disaster is a phenomenon that has a destructive effect and arises with or without predictions that always accompany human life. This damaging impact can be in the form of loss of life and / or property loss so that it disrupts the natural and social order. Lombok is one of the islands in the group of islands in West Nusa Tenggara. The island of Lombok is flanked by two large faults, the Flores Back Arc Thrust (FBAT) which extends north of Nusa Tenggara to Bali and Megathrust on the south of Lombok. Seeing from the great potential of earthquake disasters that can occur at any time on the island of Lombok, it is necessary to prepare disaster mitigation well in order to minimize the impact of earthquake disaster risk. From the problems outlined, the researchers plan to create a mobile-based earthquake e-standby application. This study aims to create a mobile-based earthquake e-alert application that can be used to view the latest earthquake information, information for determining the nearest evacuation location and educational media related to earthquake disaster awareness. The stages of the research use the prototype development method with stages, namely the study of literature, collection of needs, data collection, needs analysis, design, prototype implementation, prototype evaluation, implementation and testing and conclusions. The conclusion of this research is the construction of a mobile-based earthquake e-alert application. This application is useful for improving, understanding and public awareness of the risk of earthquake disasters and as an educational media to create disaster resilient communities